Renewal in European Local Democracies Puzzles, Dilemmas and Options - Schaap, Linze; Daemen, Harry; SpringerLink (Online service) (Wiesbaden : VS Verlag für Sozialwissenschaften : Imprint: VS Verlag für Sozialwissenschaften, 2012)
This book explores the dynamics of democratic reform processes in  European local government. On the basis of analyses of theoretical challenges to present developments, the book pays attention to processes of democratic innovation inspired by classical representative democracy and by new forms of democracy influenced by notions of governance, participation, e-governance, empowering civil society and the like.  Also attention is given to the role of regionalization and of leader- ship in efforts to revitalize local democracy. Cases from all over Europe are being studied.
Puzzles of Local Democracy -- Revitalising Representative Democracy -- Tensions and New Connections between Participatory and Representative Democracy in Local Governance -- E-forums: Refreshing the Representative Relationship? -- A New Position for Civil Society and Citizens? -- Strong Leadership and Local Democracy: Rivals or Potential Allies? -- The Added Value of Intra-municipal Decentralisation: Comparing Bologna, Rotterdam, and Birmingham -- Regionalisation and the Democratic Legitimacy of Local Governments -- The Dynamics of Democratic Learning.
Keywords: Political science; Political Science